Exploring the biological activity of condensed tannins and nutritional value of tree and shrub leaves from native species of the Argentinean Dry Chaco - García, Elisa Mariana; Cherry, Nicole; Lambert, Barry D.; Muir, James P.; Nazareno, Mónica Azucena; Arroquy, Jose Ignacio (2018)
BACKGROUND: Tropical tree or shrub leaves are an important source of nutrients for ruminants and a potential source of biologically active compounds that may affect ruminalmetabolism of nutrients. Therefore, eightwoody species fromthe native flora ofArgentinean Dry Chaco, rich in secondary compounds such as condensed tannins (CT),were assessed for their nutritional value, CT fractions and in vitro true digestibility of dry matter, as well as biological activity (BA). RESULTS: Differencesamongspecieswere foundin contents of total phenol, protein-precipitating phenols (PPP),boundproteins to PPP (BP) and BP/PPP (P<0.0001). The BP/PPP ratio reveals differences among species in potential BA as indicated by protein precipitation. The major CT of each species were isolated and purified for use as a standard. Although Schinopsis balansae had themost (P≤0.05) total CT (19.59% DM), Caesalpinia paraguariensis had greater (P≤0.05) BA with themost PPP (530.21% dry matter). Larrea divaricata, at 0.97, followed by Acacia aroma, at 0.89, had CT with the highest (P≤0.05) BP/PPP ratios, followed by Prosopis alba (0.59). CONCLUSION: There were differences in nutritive value and bioactivity among species. Those with the greatest CT were not necessarily thosewith the most BA. Caesalpinia paraguariensis, S. balansae and L. divaricatawere themost promising species as native forage CT sources. Cercidiurm praecox (20.87% CP; 18.14% acid detergent fiber) and Prosopis nigra (19.00% CP; 27.96% acid detergent fiber) showed the best (P≤0.05) nutritive values. According to their nutritive traits, these species might be complementary in grass-based ruminant diets.